Accuracy of call-taker assessment of patient level of consciousness: A systematic review - Belcher, J.; Finn, Judith; Ball, Stephen (2020)
© 2020, Paramedics Australasia. All rights reserved. Introduction When triaging an emergency phone call for ambulance assistance, one of the key areas of questions asked in internationally used triage decision support systems is around the patient’s level of consciousness. A patient with a reduced level of consciousness can be indicative of a requirement for a high level of urgency of ambulance response. However, the value of this as a triage criterion is dependent on how accurately it can be determined by the call-taker. We sought to identify and summarise the results from published studies which determine the accuracy of call-taker assessment of conscious state during an emergency phone call. Methods We searched MEDLINE, EMBASE, CINAHL and Scopus databases for studies relating to concepts of emergency medical services, conscious state, triage and/or accuracy. Studies were screened and included if they dealt with emergency calls in the community, reported call-taker determination and on-scene determination of conscious state, and included sufficient data for at least one measure of diagnostic accuracy to be calculated. Results Out of 5753 articles initially identified, only two were found that matched the inclusion criteria. Both reported accuracy of a binary determination of consciousness versus unconsciousness, and found that it is common for the reported consciousness to differ from actual findings at scene. There were no studies identified that measured accuracy of determination of altered conscious states among conscious patients. Conclusion There is a notable gap in the literature regarding accuracy of determination of the patient’s conscious state in an emergency call, which needs to be addressed.